Atmosfere metropolitane : La Generazione delle Immagini VI. - Brandirali, Aldo; Gallo, Rubén; Jouannais, Jean-Yves; Kellner, Clive; Koop, Stuart; Kortun, Vasif; Manchester, Clare; Nagy, Peter; Perán, Marti; Pinto, Roberto; Poshyananda, Apinan; Simans, Franklin; et al. (Milano : Comune di Milano, 2001)
Cuevas, Minerva ; Brugemann, Stefan ; Hernandez, Jonathan ; Jodna, Samar S. ; Singh, Dayanita ; Singh, Pamela ; Gupta, Sunil ; Benglis, Lynda ; Sharma, Satish ; Krishnamachari, Bose ; Rahman, Ram ; Sundaram, Vivan ; Lochan, Rajeev ; Chhachhi, Sheba ; Garaicoa, Carlos ; Bruguera, Tania ; La Plastica ; Delgado, Angel ; Tonel ; Toirac, José Angel ; Leal, Ernesto ; Pujol, Ernesto ; Ramos, Sandra ; Garaicoa, Carlos ; Miranda, Ibrahim ; Gonzalez, Abigail ; Pina, Manuel ; Kcho ; Rawanchaikul, Navin ; Sriwanichpoom, Manit ; Plienbangchang, mongkol ; Shawanasai, Michael ; Ing K. ; Puipia, Chatchai ; Toemsombat, Montri ; Onur, Halan ; Sangar, Bülent ; Yediler, Iskender ; Tuna, Vahit ; Saglam, Sefa ; Alptekin, Hüseyin ; Incirlioglu, Guven ; Birsel, Selim ; Cekil, Cengiz ; Avsar, Vahap ; Karamustafa, Gülsün ; Murtezaoglu, Aydan ; Özseçen, Ebru ; Aballi, Ignasi ; Comeron, Octavi ; Domènec ; Morey, Joan ; Partegas, Ester ; Duran, Pep ; Soto, Montserrat ; Martin, Josep Maria ; Rivalta, Jorge ; Maso, Mireya ; Capllonch, Biel ; Langhton, Chris ; Morton, Callum ; Weaver, Louise ; Beynon, Kate ; A Constructed World ; Foley, Fiona ; Jones, Jennie c. ; Moscouw, Micheala ; Hargraves, Jeff ; Agbay Cherubini, Nicole ; Lynn Harris, Kira ; Coen, Nadia ; Odita, Donald ; Arenas Ilian, Adriana ; Galegati, Stefania ; Matei, Laura ; Berti, Simone ; Matoga, Katarzyna ; Ligorio, Deborah ; Takahashi, Tomoko ; Leckey, Mark ; Webber, Dennis ; Deller, Jeremy ; Glendenning, Hugo ; Creed, Martin ; Griffiths, Brian ; Franks, Matthew ; Daly, Pauline ; Macmillan, Tim ; Inventory ; Webster, Sue ; Noble, Tim ; Geers, Kendell ; Mtethwa, Zwelethu ; Schonfeldt, Joachim ; Boshoff, William ; Alvim, Fernando ; Krog, Antjëe ; Loots, Ronelle ; Vari, Minnette ; Williamson, Sue
Italiaans & Engels
Atmosfere metropolitane : La Generazione delle Immagini VI, Comune di Milano, 1999-2000
boek